EVALUASI PENGHITUNGAN PAJAK PENGHASILAN PASAL 21 (STUDI KASUS PADA DINAS PUPR PROVINSI MALUKU UTARA) - Ningrum, Tiara; Ilat, Ventje; Pontoh, Winston (GOING CONCERN : JURNAL RISET AKUNTANSI, 2020)
In improving peopleâ€™s welfare and national development, the government requires regular acceptance. In the state budget (APBN) the biggest source of revenue is from the tax sector. Tax is a mandatory contribution that is imposed on every tax payer on the object it has and the result are submitted to the government. North Maluku Public Works and Public Housing Office is one on the regional apparatus that has a number of employees with the specification of civil servants (state civil servants) and regional honorary employees, so that it has great potential in paying taxes, especially article 21 of the income tax. in addition, the office of Public Works and Public Housing in North Maluku Province also has the potential to cause irregularities in the calculation of income tax due to differences in views on the Income Tax Law. this is the research reference with the title â€œEvaluation Of Article 21 Income Tax Calculation For Civil Servants in the Public Works and Public Housing Agency of North Maluku Provincesâ€. The purpose of this study is to determine the Calculation of Income Tax Article 21 for Civil Servants in the Public Works and Public Housing Office of North Maluku Province has been appropriate and in accordance with applicable laws and regulation. The method used in this research is quantitative descriptive method. Calculation of Income Tax Article 21 of civil servants salaries at the Department Public Works and Public Housing in North Maluku has been carried out correctly and in accordance with the provisions of the applicable Taxation Law.Â Article 21 for Civil Servants in the Public Works and Public Housing Office of North Maluku Province has been appropriate and in accordance with applicable laws and regulation. The method used in this research is quantitative descriptive method. Calculation of Income Tax Article 21 of civil servants salaries at the Department Public Works and Public Housing in North Maluku has been carried out correctly and in accordance with the provisions of the applicable Taxation Law.